A Comprehensive Review of the Chemistry, Pharmacokinetics, Pharmacology, Clinical Applications, Adverse Events, and Quality Control of Indigo Naturalis - Sun, Quan; Leng, Jing; Tang, Ling; Wang, Lijuan; Fu, Chaomei (Frontiers in Pharmacology, 2021)
Indigo naturalis (IN), which is derived from indigo plants such as Strobilanthes cusia (Nees) Kuntze, Persicaria tinctoria (Aiton) Spach and Isatis tinctoria L., has been traditionally used in the treatment of haemoptysis, epistaxis, chest pain, aphtha, and infantile convulsion in China for thousands of years. Clinical trials have shown that the curative effect of IN for psoriasis and ulcerative colitis (UC) is remarkable. A total of sixty-three compounds, including indole alkaloids, terpenoids, organic acids, steroids, and nucleosides, have been isolated from IN, of which indole alkaloids are the most important. Indirubin, isolated from IN, was used as a new agent to treat leukaemia in China in the 1970s. Indirubin is also an active ingredient in the treatment of psoriasis. Pharmacological studies have confirmed that IN has inhibitory effects on inflammation, tumours, bacteria and psoriasis. Indigo, indirubin, tryptanthrin, isorhamnetin, indigodole A and indigodole C are responsible for these activities. This review provides up-to-date and comprehensive information on IN with regard to its chemistry, pharmacokinetics, pharmacology, clinical applications, adverse events and quality control. This review may also serve a reference for further research on IN.